2017
DOI: 10.1080/20008198.2017.1338106
|View full text |Cite
|
Sign up to set email alerts
|

A virtual reality paradigm as an analogue to real-life trauma: its effectiveness compared with the trauma film paradigm

Abstract: Background: The trauma film paradigm (TFP) is a well-established method to study the effects of analogue psychological trauma under controlled laboratory settings. It has been used to examine pre-, peri-, and post-trauma processes, and to create and test interventions. A possible drawback is that watching films is a somewhat passive endeavour that lacks active behavioural engagement. Virtual reality (VR) may provide a better alternative. Like the TFP, VR allows for experimental control. In addition, it can ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…Future studies may explore whether TI also affects voluntary memory. For example, a previous study found different effects on vividness and emotionality of voluntary recollections but not on the frequency of involuntary intrusive memories (Cuperus, Klaassen, Hagenaars, & Engelhard, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Future studies may explore whether TI also affects voluntary memory. For example, a previous study found different effects on vividness and emotionality of voluntary recollections but not on the frequency of involuntary intrusive memories (Cuperus, Klaassen, Hagenaars, & Engelhard, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Due to the negative effects on the emotional and physical state of the subjects, it is necessary to follow strict ethical requirements, and it is also difficult to attract subjects to participate in such study. Investigations of pre-, peri-, and posttraumatic processes in the VR paradigm have revealed that VR content induces traumatic stress [23], and they also showed that stressful VR content causes mild stress symptoms, such as those related to trauma thoughts and beliefs, intrusion, and avoidance behavior [24,25]. The assumption that people with OCD, PTSD, and psychotic disorders are more vulnerable to cybersickness has previously been put forward, but when tested, conflicting results were received.…”
Section: Introductionmentioning
confidence: 99%
“…Cuperus, Klaassen, Hagenaars, and Engelhard (2016) evaluated informative hypotheses using BIEMS regarding the use of virtual reality (VR) in the TFP using BFs. With the TFP, the effects of psychological trauma can be studied under controlled experimental settings.…”
Section: Special Issuementioning
confidence: 99%